Prominent Muslim da`wah figures and their global role in changing the perception of Islam - Aswar, Hasbi; Febrian, Silvia Jultikasari; Alfayed, Nazila; Safitri, Auliya Eka (Communications in Humanities and Social Sciences, 2023)
Amidst the escalating negative narrative surrounding Islam, there is a parallel increase in efforts by Muslim figures and communities to counteract these perceptions. Leveraging the expansive reach of social media, influential personalities like Zakir Naik, Mufti Menk, and Nouman Ali Khan engage global audiences, including non-Muslim communities. This article explores how these figures impact the transformation of global perceptions of Islam through da`wa on online platforms, employing the concept of people-to-people diplomacy as an analytical tool. Data, primarily sourced from online platforms, media, books, and journals, reveal that these Muslim figures have significantly contributed to alter the global perceptions of Islam. Their efforts play a crucial role in gradually shifting non-Muslims from a stance of prejudice to one of empathy, fostering a more nuanced understanding of Islam worldwide.